Low temperature storage of NAA, GA3 and 2,4-D treated citrus budsticks (Scientia Agricola, 2008)
Cold storage allows citrus budstick conservation for several months, although gradual bud viability loss and abscission of leaf petioles is observed. This study aimed to maintain bud viability reducing leaf petiole abscission in budsticks of 'Baianinha' and 'Valencia' sweet oranges (C. sinensis Osbeck), 'Tahiti' lime (C. latifolia Tanaka), and 'Murcott' tangor (C. sinensis × C. reticulata), using NAA, GA3, 2,4-D, and low temperature storage. After a 15-minutes-immersion in distilled water and NAA and GA3 solutions at concentrations of 10, 100, 500 and 1000 µmol L-1, and 2,4-D solutions at concentrations of 1, 10, 50 and 100 µmol L-1, the shoots were stored in polyethylene bags at 5 ± 1ºC for 74 days. Percentage of leaf petiole abscission, fresh and dry matter losses, bud viability, and growth flush were evaluated. NAA and 2,4-D had the highest efficiency for petiole abscission inhibition, reaching almost 99% of success. The packaging system and shoot storage under low temperature efficiently reduced fresh and dry matter losses. Bud viability of 'Baianinha', 'Valencia' and 'Murcott' shoots was not reduced by storage, maintaining above 95% of grafting success. NAA, GA3 and 2,4-D treatments had no influence on sprout growth.